Entertainment industry economics : a guide for financial analysis - Vogel, Harold L., 1946- (Cambridge : Cambridge University Press, 2020)
Already among the most important sectors of the US economy, the entertainment and media industries are continuing to grow worldwide. Fully updated, the tenth edition of Entertainment Industry Economics is the definitive reference on the economics of film, music, television, advertising, broadcasting, cable, casinos, publishing, arts and culture, performing arts, toys and games, sports, and theme parks. Its synthesis of a vast amount of data provides an up-to-date guide to the economics, financing, accounting, production, marketing, and history of these sectors in the United States and countries across the globe. This edition offers new material on streaming services, the relationship between demographics and entertainment spending, electromagnetic spectrum for broadcasters, and revised FASB accounting rules for film and television. Financial analysts and investors, economists, industry executives, accountants, lawyers, regulators, and journalists, as well as students preparing to join these professionals will benefit from this invaluable source.
Title from publisher's bibliographic system (viewed on 29 Jun 2020).
Keywords: elektronické knihy; electronic books; Performing arts -- Finance